Mesenchymal Stem Cells Overexpressing ACE2 Favorably Ameliorate LPS-Induced Inflammatory Injury in Mammary Epithelial Cells - Yan, Shuping; Ye, Pingsheng; Aleem, Muhammad Tahir; Chen, Xi; Xie, Nana; Zhang, Yuanshu (Frontiers in Immunology, 2022)
Mesenchymal stem cells (MSCs) are capable of homing injury sites to exert anti-inflammatory as well as anti-damage effects and can be used as a vehicle for gene therapy. Angiotensin-converting enzyme 2 (ACE2) plays an important role in numerous inflammatory diseases, but fewer studies have been reported in animal mastitis. We hypothesized that MSCs overexpressing ACE2 is more effective in ameliorating lipopolysaccharide (LPS)-induced inflammatory injury in mammary epithelial cells compared to MSCs alone. The results showed that MSC-ACE2 inhibited the LPS induction by upregulation of TNF-α, IL-Iβ, IL-6, and iNOS mRNA expression levels in EpH4-Ev cells compared with MSCs. Furthermore, results showed that both MSC and MSC-ACE2 were significantly activated IL-10/STAT3/SOCS3 signaling pathway as well as inhibited TLR4/NF-κB and MAPK signaling pathways, but MSC-ACE2 had more significant effects. Meanwhile, MSC-ACE2 promoted the expression of proliferation-associated proteins and inhibited the expression of the apoptosis-associated proteins in EpH4-Ev cells. In addition, MSC and MSC-ACE2 reversed the LPS-induced downregulation expression levels of the tight junction proteins in mammary epithelial cells, indicating that both MSC as well as MSC-ACE2 could promote blood-milk barrier repair, and MSC-ACE2 was more effective. These results suggested that MSCs overexpressing ACE2 were more anti-inflammatory as well as anti-injurious action into LPS-induced inflammatory injury in the EpH4-Ev cells. Thus, MSCs overexpressing ACE2 is expected to serve as a potential strategy for mastitis treatment.